Application of response surface methodology for silver nanoparticle stir bar sorptive extraction of heavy metals from drinking water samples: a Box–Behnken design. Issue 11 (25th April 2019) - Hashemi, Sayyed Hossein; Kaykhaii, Massoud; Jamali Keikha, Ahmad; Sajjadi, Zahra; Mirmoghaddam, Majid
Abstract : Silver nanoparticles were coated on a glass stir bar and used for the extraction of heavy metals from water samples after their complexation with ligand PAN, followed by their HPLC determination. Abstract : Silver nanoparticles were coated on a glass stir bar by overnight exposure of the bar to the nanoparticle solution, using 3-aminopropyltriethoxysilane as a binding agent and were used for the extraction of heavy metal Fe 3+, Cu 2+, Pb 2+ and Zn 2+ cations from water samples after their complexation with the ligand 1-(2-pyridylazo)-2-naphthol, followed by their determination by high performance liquid chromatography. Various parameters affecting the extraction were evaluated by one variable-at-a-time and Box–Behnken design methods and optimized. Six independent variables, the pH and ionic strength of the solution, the Triton X-114 (surfactant) concentration, amount of ligand, and adsorption and desorption times, were coded as A, B, C, D, E and F at three various levels (−1, 0, and 1). The linear ranges of the technique were 0.5–250.0 μg L −1 for all four analytes. Under the optimum conditions, the limits of detection were calculated as 0.08, 0.11, 0.12 and 0.17 μg L −1 for copper, iron, lead and zinc, respectively. The technique was used for the determination of these cations in drinking water samples.